THE EFFECT OF METHIONINE ADDITION TO INCREASE MONACOLIN K PRODUCTION IN Monascus purpureus SOLID FERMENTATION FROM ANGKAK RICE IN MARKET - Yulia, Nunung
Background and Purpose: Monascus Fermented Rice (MFR= angkak) is the fermentation product of rice by a fungus Monascus purpureus. Fermentation of red yeast rice produces monacolin K or lovastatin anticholesterol compounds, but until today, the efforts to produce monakolin K constrained by its low yield. The purpose of this study was to identify and analyze one of the secondary metabolites, monacolin K, from M. purpureus which obtained from several red yeast rice that sold in some supermarkets in Bandung, and to increase the productivity of monacolin K from M. purpureus with addition of the methionine. Method: M. purpureus from some red yeast rice were grown on PDA, then they were identified macroscopically and microscopically to determine the type of fungi from the Monascus genus. The production of inoculum is carried out based on the results of previous optimization studies using YMP medium (Yeast extract- Malt extract- Peptone) fermentation for 8 days. Inoculum was added into rice media, and fermented at temperature of 27-32 o C for 14 days. Fermented rice samples analyzed by measuring the absorbance of extract counting monakolin K, the moisture content level, and the amount of colonies. The effect of methionine additions to the monacolin K level was evaluate using HPLC method. Result: Red yeast rice produced the highest biomass of 11.3x10 3 CFU/g with water content of 16.8 % w/w. Monacolin K standard calibration curve with the regression equation of y = 3987x –1177 provides linear in the range concentration of 0.01 –1.00 mg/mL with a correlation coefficient r = 0.9979. The addition of the methionine amino acid at concentration of 0.3%w/v –1.0%w/v increased the production of monacolin K compared with no addition of the methionine amino acid at levels of 1.72 to 7.02 ?g/mg extract. Conclusion: Monascus purpureus from red yeast rice in supermarkets B is the isolate highest biomass at rice fermentation. The concentration of monacolin K in without methionine and with methionine 0.3; 0.4; 0.5; and 1%b/v were 7, 9, 11, and 19 respectively.